Philanthropy in America : a History - Zunz, Olivier (Politics and society in twentieth-century America., 2014)
American philanthropy today expands knowledge, champions social movements, defines active citizenship, influences policymaking, and addresses humanitarian crises. How did philanthropy become such a powerful and integral force in American society? Philanthropy in America is the first book to explore in depth the twentieth-century growth of this unique phenomenon. Ranging from the influential large-scale foundations established by tycoons such as John D. Rockefeller, Sr., and the mass mobilization of small donors by the Red Cross and March of Dimes, to the recent social advocacy of individuals like Bill Gates and George Soros, respected historian Olivier Zunz chronicles the tight connections between private giving and public affairs, and shows how this union has enlarged democracy and shaped history. Demonstrating that America has cultivated and relied on philanthropy more than any other country, Philanthropy in America examines how giving for the betterment of all became embedded in the fabric of the nation's civic democracy.